OVERCOMING ANXIETY THROUGH RIDHA, TAWAKKAL, AND PATIENCE: A THEMATIC STUDY IN THE TAFSIR FI ZHILALIL QUR'AN - Wan Alif Ihza Mahendra; Sahdin Hasibuan (Journal Analytica Islamica, 2025)
Anxiety disorder has become one of the most pressing mental health issues in modern society. Conventional psychological approaches such as Cognitive Behavioral Therapy (CBT), pharmacotherapy, and mindfulness often emphasize biological and rational aspects, leaving the spiritual dimension underexplored. In fact, spirituality plays an essential role in establishing psychological balance. This study aims to examine the Qur'anic values of ridha (acceptance), tawakkal (trust in God), and sabr (patience) as interpreted in Sayyid Qutb's Fi Zhilalil Qur'an, and their relevance in overcoming contemporary anxiety. This research applies a qualitative method with a library research approach, utilizing thematic exegesis (tafsir maudhū'i) of the Qur'anic verses and their interpretations, combined with Islamic psychology literature and empirical findings related to anxiety. The results indicate that ridha serves as active acceptance fostering emotional stability, tawakkal harmonizes human effort with reliance on God to generate inner peace, and sabr strengthens psychological resilience in facing life's challenges. The integration of these three values forms a holistic Qur'an-based Islamic therapeutic model that is both normative and applicable. Therefore, this study highlights the significance of Qur'anic spirituality as an alternative framework for addressing anxiety while simultaneously reinforcing the spiritual foundation of modern Muslim communities.